2011 Presidential Address of the Canadian Historical Association: Historians without Borders / 2011 Discours de la présidente de la Société historique du Canada : historiennes et historiens sans frontières - Stewart, Mary (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
Using her own experience as a window into the experiences of many historians, and especially women historians, who entered the profession in the 1960s, Mary Lynn spotlighted four barriers this generation crossed. First, many who came from working-class families benefitted from the expansion of university studies and financial support to take degrees, especially in the liberal arts as opposed to more practical diplomas that our parents and families preferred. They brought with them an interest in those who had been left out of conventional histories, thereby developing the fields of labour, social, and women’s history. Second, many participated in the political and social protests of the 1960s and learned from this much about the operations of power and memory that would apply in historical research and analyses. Third, women and men who were involved in the women’s movement in the 1960s and 1970s opened up the field of women’s history and subsequently gender history. Fourth, they did more local, regional and, more recently, transnational historical studies and within history departments, pressed for more inclusive and representative faculty members to teach the more expansive kind of history that has emerged.